Fragility of secured credit chains - Piero Gottardi; Vincent Maurin; Cyril Monnet (University of Bern, Department of Economics, 2023)
We present a model of secured credit chains in which assets generated from intermediation activity and pledged as collateral create fragility. A dealer stands between a borrower and a financier. The dealer borrows from the financier to fund her project, subject to a moral hazard problem, In addition, the dealer can intermediate between the financier and the borrower, forming a credit chain. Intermediation profits can thus act as collateral for the loan to fund the dealer's own project. When these profits are risky, however, using them as collateral may undermine the dealer's incentives, generating fragility in the chain. The arrival of news about the value of the revenue of the intermediation activity further increases fragility. This fragility channel generates a premium for safe or opaque collateral. The environment considered in our model applies to various situations, such as trade credit chains, securitization and repo markets.
Keywords: G23; G30; 330; Collateral; Secured Lending; Intermediation; Fragility